2015
DOI: 10.1093/protein/gzv028
|View full text |Cite
|
Sign up to set email alerts
|

Substitutions at the cofactor phosphate-binding site of a clostridial alcohol dehydrogenase lead to unexpected changes in substrate specificity

Abstract: Changing the cofactor specificity of an enzyme from nicotinamide adenine dinucleotide 2′-phosphate (NADPH) to the more abundant NADH is a common strategy for increasing overall enzyme efficiency in microbial metabolic engineering. The aim of this study was to switch the cofactor specificity of the primary–secondary alcohol dehydrogenase from Clostridium autoethanogenum, a bacterium with considerable promise for the bio-manufacturing of fuels and other petrochemicals, from strictly NADPH-dependent to NADH-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…Mutagenesis study demonstrated that the sole mutation of the Leu 36 into aspartic acid residue indeed changed the cofactor preference of 17β‐HSD1 from NADP(H) to NAD(H) , and eliminated the substrate inhibition of the enzyme in the presence of NADPH . Although the (phosphor‐)adenosine moiety of NADP is distal from the catalytic site of the enzyme, subtle perturbations to the (phosphor‐) adenosine binding pocket was proved to have a dramatic effect on activity and mutations at the 2′‐phosphate binding site was demonstrated to affect substrate specificity . Thus the stabilization of the 2′‐phosphate group of NADPH is essential for maintaining the substrate inhibition in 17β‐HSD1.…”
Section: Discussionmentioning
confidence: 98%
“…Mutagenesis study demonstrated that the sole mutation of the Leu 36 into aspartic acid residue indeed changed the cofactor preference of 17β‐HSD1 from NADP(H) to NAD(H) , and eliminated the substrate inhibition of the enzyme in the presence of NADPH . Although the (phosphor‐)adenosine moiety of NADP is distal from the catalytic site of the enzyme, subtle perturbations to the (phosphor‐) adenosine binding pocket was proved to have a dramatic effect on activity and mutations at the 2′‐phosphate binding site was demonstrated to affect substrate specificity . Thus the stabilization of the 2′‐phosphate group of NADPH is essential for maintaining the substrate inhibition in 17β‐HSD1.…”
Section: Discussionmentioning
confidence: 98%
“…However, in many cases the mutations do not achieve the desired effect, cause the loss of catalytic activity or lead to unexpected results [185,186]. This is partially due to the lack of understanding of the relationship between the amino acid sequence of a protein, its structure and its function, which still prevents us from developing widely applicable methodologies to alter the substrate or cofactor specificity of oxidoreductases.…”
Section: Protein Engineeringmentioning
confidence: 99%
“…-1.1 (Kristan et al 2007) C. lunatus BHSDH 3QWF Y49D 7.8 ? -4.2 (Liang et al 2007) P. stipitis XR 1K8C (h) K270R, N272D 2.9 9.3 -1.2 (Maddock et al 2015) E. coli CaADH 1KEV (h) G198D, S199V, P201E, Y218A >1 ? -4.6 (Maurer et al 2005) B Log Relative Activity c (Medina et al 2001) A. PCC7119 FDNR 2BSA S223D 0.12 8.1x10 3 -5.4 (Nakanishi et al 1997) M. musculus CR 1CYD T38D 31 1.3x10 3 -0.51 (Paladini et al 2009 (Schepens et al 2000) S. bicolor MDH 7MDH (1CIV) G84D, S85I, R87Q, S88A 12 2.1x10 4 -0.96 (Scrutton et al 1990) E. coli GTR 1GET A179G, A183G, V197E, R198M, K199F, H200D, R204P 8.1 1.8x10 4 -1.5 (Shiraishi et al 1998) N. crassa CbR S920D, R932S 65 7.2x10 4 -2.6 (Takase et al 2014) S. sp.…”
mentioning
confidence: 99%